2007
DOI: 10.1111/j.1365-2559.2007.02576.x
|View full text |Cite|
|
Sign up to set email alerts
|

Association of COX‐2 expression with corresponding active and chronic inflammatory reactions in Barrett's metaplasia and progression to cancer

Abstract: Increasing COX-2 expression in Barrett's metaplasia is significantly associated with a change in the local inflammatory reaction, but not during further progression through dysplasia to cancer. This supports the potential of a chemoprevention strategy using COX-2 inhibitors independent of the extent and type of the inflammatory reaction in Barrett's oesophagus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Theoretically, the difference between COX-2 expression and Met expression as prognostic indicators can probably be explained by their function. The COX-2 enzyme is enhanced in inflammation and has been shown to be involved in early progression of oesophageal metaplasia and dysplasia into (adeno-) carcinoma (Morris et al, 2001;Buskens et al, 2002;Abdalla et al, 2004;Ling et al, 2007). Increased COX-2 expression causes activation of several cancer-related genes including the HGF receptor Met (Boon et al, 2004;Han et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Theoretically, the difference between COX-2 expression and Met expression as prognostic indicators can probably be explained by their function. The COX-2 enzyme is enhanced in inflammation and has been shown to be involved in early progression of oesophageal metaplasia and dysplasia into (adeno-) carcinoma (Morris et al, 2001;Buskens et al, 2002;Abdalla et al, 2004;Ling et al, 2007). Increased COX-2 expression causes activation of several cancer-related genes including the HGF receptor Met (Boon et al, 2004;Han et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported the absence of COX-2 immunostaining in normal epithelium (20,21,28,36) . Our results agree with those reported by JACKSON et al (17) who observed COX-2 expression in normal gastric mucosa.…”
Section: A B C Dmentioning
confidence: 99%
“…At the histological level, its defining feature is the presence of goblet cells, similar to those of the epithelium of the small intestine and colon. Barrett's metaplasia is characterized by active as well as chronic inflammation [11] suggesting that inflammation contributes to the BE field defect.…”
Section: Esophageal Adenocarcinomamentioning
confidence: 99%